Isolation of Mesenchymal Stem Cells from Adipose Tissue - Harsan Harsan; Silmi Mariya; Andi Asadul Islam; Eka Julianta Wahjoepramono; Irawan Yusuf (The Indonesian Biomedical Journal, 2015)
BACKGROUND: In searching for the best source of stem cells, researcher found adipose stem cells as one of the ideal source due to its easiness in harvesting and its potential for differentiating into other cell lineage.METHODS: We isolated stem cells from adipose tissue, cultured and confirmed its immunophenotype using polymerase chain reaction.RESULTS: Cluster of differentiation (CD)44, CD73, CD90, CD105 were expressed, which represent immunophenotype of mesenchymal stem cells. CONCLUSION: Mesenchymal stem cells can be isolated from adipose tissue. KEYWORDS: adipose, mesenchymal stem cells, isolation, immunophenotype